(untitled) (Palíndromo, 2013)
The Montage issue is dealt as an important procedure in the Leya Mira Brander’s graphic work, an artist from São Paulo. Avoiding a simple homogenization, seeks to consider the following aspects related to the Montage: by time serialization, by anachronism, by juxtaposition, by collage, by superposition, by deductive superposition and by agglomeration.